Teachers’ Pedagogical Competence as a Strong Predictor of Learning Quality in Elementary Education - Yatini Yatini; Supandi Supandi; Nurkolis Nurkolis (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study investigates the effect of teachers’ pedagogical competence on learning quality in public elementary schools in Tanggungharjo Subdistrict, Grobogan Regency. Employing a quantitative correlational design, the study involved 137 teachers selected through proportional random sampling. Data were collected using validated and reliable questionnaires measuring pedagogical competence and learning quality, and were analyzed using Pearson correlation and simple linear regression with SPSS. The findings reveal a positive and significant relationship between pedagogical competence and learning quality (r = 0.832; p < 0.001), indicating a very strong association. The coefficient of determination shows that pedagogical competence contributes 69.3% to the variance in learning quality. The regression equation (Y = 27.769 + 1.045X) suggests that improvements in pedagogical competence are directly followed by increases in learning quality. These results highlight the critical role of pedagogical competence as a key determinant of instructional effectiveness and emphasize the importance of targeted professional development programs to enhance teaching quality in elementary education.